EVIDANCE BASED CASED REPORT (EBCR) TERAPI FOOT MASSAGE DAPAT MENURUNKAN INTENSITAS NYERI POST OPERASI SEKSIO SESAREA (Jurnal Kesehatan Siliwangi, 2023)
Childbirth can be done in two ways, namely normal or spontaneous delivery and assisted delivery (Section Caesarea). In the process of cesarean section, surgery is carried out in the form of an incision in the abdomen and uterus to remove the baby. Caesarean section delivery usually experiences excessive pain compared to normal delivery, therefore management of pain management is needed to overcome the problem of post-operative pain section by Caesarean section. Foot massage is a non-pharmacological treatment for postoperative abdominal pain, because there are many nerves connected to the internal organs in the foot area. The purpose of this evidence-based case study was to determine the effectiveness of foot massage therapy on pain intensity in postoperative cesarean section patients. This journal search method uses E-data based PubMed and Science Direct with the year of publication 2012-2022 which meets the inclusion and exclusion criteria through the Randomized Controlled Trial design. The results of this evidence-based case study found that there was a decrease in pain levels in post-cesarean section postoperative patients by providing foot massage therapy for 20 minutes. Thus, it can be concluded that giving foot massage therapy is effective in reducing pain intensity in postoperative cesarean section patients